Of zinc roofs and mango trees: tractors, the state and agrarian dualism in Mozambique - Cabral, Lídia (The Journal of Peasant Studies, 2021)
This paper reviews the latest mechanisation programme by the Mozambican government, asking how it is politically driven and how it shapes and is shaped by agrarian structures. Old ideas about agrarian dualism are reproduced today, albeit with a new language of public-private partnerships that are seen as potentially driving the modernisation of the peasantry. State-sponsored and privately-run service centres, featuring zinc roofed warehouses, are the government’s preferred route to modernisation, yet failing to reach the average farmer and understanding the motives and predicaments of private managers. Emerging small to medium farmers, who keep tractors under shady mango trees in their backyards, are also offering mechanisation services to their peers, which are instrumental to stepping up their production and commercial activities. The state’s push for mechanisation feeds uneven patterns of accumulation and social differentiation.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150.2020.1860026
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; agriculture / agricultura; government policy / politica governamental; private sector / setor privado

Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic: Synthesis and policy recommendations - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions, 2020)
We now proceed to bringing together the different elements of previous chapters with the aim of presenting the essence of this country study of Mozambique. In the next section, we take stock and revisit our points of departure from Chapters 2 and 3. This background work culminated in the identification of nine thematic areas, subsequently subjected to individual in-depth studies in Chapters 4–12. We outline the core findings from these studies, and present our integrated analysis of key institutional weaknesses. Next, we go a decisive step further, and analyse and discuss their proximate causes and deep factors. We end with a series of ideas for reform, as an input to national reflection, debate, and action.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; ⛔ No DOI found

O sector da educação em Moçambique: do acesso à qualidade epistémica do ensino primário - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Desde os primeiros anos de independência nacional, em 1975, o objectivo central da política educativa de Moçambique tem sido o de assegurar que todas as crianças em idade escolar tenham acesso à escola e nela permaneçam até concluírem a educação básica. Na prossecução deste objectivo, a expansão do acesso ao ensino primário foi realizada com relativo sucesso, uma vez que já se alcançou uma taxa líquida de cobertura escolar de quase 100%. Contudo, o impressionante aumento das taxas de escolarização não tem sido acompanhado por uma correspondente melhoria da qualidade da aprendizagem, havendo, em relação a este aspecto, sinais preocupantes de um retrocesso considerável. Partindo desta observação, o estudo identifica e analisa as variáveis do contexto institucional por detrás da 'escolarização sem aprendizagem'. Os resultados do estudo apontam para a (i) fraca capacidade do Estado, (ii) excessiva dependência da ajuda externa e (iii) fraco envolvimento e participação das comunidades na gestão das escolas, como sendo os factores de maior influência na fraca qualidade da aprendizagem no ensino primário.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The education sector in Mozambique: From access to epistemic quality in primary education - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Abstract: From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind ‘schooling without learning’. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

How do decision-makers use evidence in community health policy and financing decisions? A qualitative study and conceptual framework in four African countries - Kumar, Meghan Bruce; Taegtmeyer, Miriam; Madan, Jason; Ndima, Sozinho; Chikaphupha, Kingsley; Kea, Aschenaki; Barasa, Edwine (Health Policy and Planning, 2020)
Various investments could help countries deliver on the universal health coverage (UHC) goals set by the global community; community health is a pillar of many national strategies towards UHC. Yet despite resource mobilization towards this end, little is known about the potential costs and value of these investments, as well as how evidence on the same would be used in related decisions. This qualitative study was conducted to understand the use of evidence in policy and financing decisions for large-scale community health programmes in low- and middle-income countries. Through key informant interviews with 43 respondents in countries with community health embedded in national UHC strategies (Ethiopia, Kenya, Malawi, Mozambique) and at global institutions, we investigated evidence use in community health financing and policy decision-making, as well as evidentiary needs related to community health data for decision-making. We found that evidence use is limited at all levels, in part due to a perceived lack of high-quality, relevant evidence. This perception stems from two main areas: first, desire for local evidence that reflects the context, and second, much existing economic evidence does not deal with what decision-makers value when it comes to community health systems—i.e. coverage and (to a lesser extent) quality. Beyond the evidence gap, there is limited capacity to assess and use the evidence. Elected officials also face political challenges to disinvestment as well as structural obstacles to evidence use, including the outsized influence of donor priorities. Evaluation data must to speak to decision-maker interests and constraints more directly, alongside financiers of community health providing explicit guidance and support on the role of evidence use in decision-making, empowering national decision-makers. Improved data quality, increased relevance of evidence and capacity for evidence use can drive improved efficiency of financing and evidence-based policymaking.
Keywords: G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

A framework on the emergence and effectiveness of global health networks - Shiffman, Jeremy; Quissell, Kathryn; Schmitz, Hans Peter; Pelletier, David L; Smith, Stephanie L; Berlan, David; Gneiting, Uwe; Van Slyke, David; Mergel, Ines; Rodriguez, Mariela; Walt, Gill (Health policy and planning, 2016)
Since 1990 mortality and morbidity decline has been more extensive for some conditions prevalent in low- and middle-income countries than for others. One reason may be differences in the effectiveness of global health networks, which have proliferated in recent years. Some may be more capable than others in attracting attention to a condition, in generating funding, in developing interventions and in convincing national governments to adopt policies. This article introduces a supplement on the emergence and effectiveness of global health networks. The supplement examines networks concerned with six global health problems: tuberculosis (TB), pneumonia, tobacco use, alcohol harm, maternal mortality and newborn deaths. This article presents a conceptual framework delineating factors that may shape why networks crystallize more easily surrounding some issues than others, and once formed, why some are better able than others to shape policy and public health outcomes. All supplement papers draw on this framework. The framework consists of 10 factors in three categories: (1) features of the networks and actors that comprise them, including leadership, governance arrangements, network composition and framing strategies; (2) conditions in the global policy environment, including potential allies and opponents, funding availability and global expectations concerning which issues should be prioritized; (3) and characteristics of the issue, including severity, tractability and affected groups. The article also explains the design of the project, which is grounded in comparison of networks surrounding three matched issues: TB and pneumonia, tobacco use and alcohol harm, and maternal and newborn survival. Despite similar burden and issue characteristics, there has been considerably greater policy traction for the first in each pair. The supplement articles aim to explain the role of networks in shaping these differences, and collectively represent the first comparative effort to understand the emergence and effectiveness of global health networks.
Edition: 2015/08/29 Publisher: Oxford University Press
Keywords: L - english / inglês; collaboration / colaboração; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde